Man – Animal – Thing in Władysław Reymont’s The Peasants - Brzozowska, Sabina (Porównania, 2021)
Reymont’s novel places humans, animals and plants in one order – the order of nature. Relations between people and animals shimmer with ambivalences, however. On the one hand, there is a somatic community between women and cows, which is the foundation of empathetic care for another being emerging in forms of tenderness. On the other hands, the novel depicts scenes of spontaneous and vacuous cruelty to wild animals, such as magpies, hares, bee-eaters (blinded with tar), etc. and their clear reification (animal – “mechanic” toy). The objective of the paper is the presentation of the complex and ambiguous nature of interspecies relations.